2014
DOI: 10.1007/s00709-014-0614-3
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium and lead interactive effects on oxidative stress and antioxidative responses in rice seedlings

Abstract: Interactive effects of two heavy metal pollutants Cd and Pb in the growth medium were examined on their uptake, production of reactive oxygen species (ROS), induction of oxidative stress and antioxidative defence responses in Indica rice (Oryza sativa L.) seedlings. When rice seedlings in sand culture were exposed to 150 μM Cd (NO3)2 or 600 μM Pb (CH3COO)2 individually or in combination for 8-16 days, a significant reduction in root/shoot length, fresh weight, relative water content, photosynthetic pigments an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
80
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(93 citation statements)
references
References 55 publications
11
80
2
Order By: Relevance
“…Heavy metals in paddy soils affect rice growth and performance; for instance, Cd stress has been proven to affect plants morphologically and physiologically as well as disrupting antioxidants enzymes in rice seedlings under polluted soils. Reports have shown reduction in rice growth and biomass, which might possibly be as a result of different Cd-mediated toxicity mechanisms in rice [10]. Various other studies have also reported that the toxic effects of Cd increased rice seedlings oxidative stress by releasing reactive oxygen species (ROS) like malondialdehyde (MDA) contents, hydrogen peroxide (H 2 O 2 ), and electrolyte leakage which affects rice growth and performance [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals in paddy soils affect rice growth and performance; for instance, Cd stress has been proven to affect plants morphologically and physiologically as well as disrupting antioxidants enzymes in rice seedlings under polluted soils. Reports have shown reduction in rice growth and biomass, which might possibly be as a result of different Cd-mediated toxicity mechanisms in rice [10]. Various other studies have also reported that the toxic effects of Cd increased rice seedlings oxidative stress by releasing reactive oxygen species (ROS) like malondialdehyde (MDA) contents, hydrogen peroxide (H 2 O 2 ), and electrolyte leakage which affects rice growth and performance [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown reduction in rice growth and biomass, which might possibly be as a result of different Cd-mediated toxicity mechanisms in rice [10]. Various other studies have also reported that the toxic effects of Cd increased rice seedlings oxidative stress by releasing reactive oxygen species (ROS) like malondialdehyde (MDA) contents, hydrogen peroxide (H 2 O 2 ), and electrolyte leakage which affects rice growth and performance [10,11]. Cadmium toxicity also altered leaf and root ultrastructure and caused structural damage to photosynthetic apparatus of rice [12].…”
Section: Introductionmentioning
confidence: 99%
“…[45]- [50]. This approach was successfully used with higher plants [41] [42] [51] however, loading of the dye into the leaf material is problematic as the procedure can cause additional stress and thus additional ROS formation as well as the distribution of the dye is rather heterogeneous.…”
Section: Photoautotrophic Response Monitoring Via Fluorescence Imagingmentioning
confidence: 99%
“…Cd stress has been proven to have some morpho-physiological and antioxidants effects in rice seedlings at the early growth stage (vegetative stage) especially in paddy polluted soils. Reports have shown reduction in rice growth and biomass, which might possibly be as a result of different Cd-mediated toxicity mechanisms in rice (Srivastava et al 2014). Other studies have reported that the toxic effects of Cd increased rice seedlings oxidative stress by releasing reactive oxygen species (ROS) like malondialdehyde (MDA) contents, hydrogen peroxide (H 2 O 2 ) and electrolyte leakage which affects rice growth and performance (Yu et al 2013;Srivastava et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown reduction in rice growth and biomass, which might possibly be as a result of different Cd-mediated toxicity mechanisms in rice (Srivastava et al 2014). Other studies have reported that the toxic effects of Cd increased rice seedlings oxidative stress by releasing reactive oxygen species (ROS) like malondialdehyde (MDA) contents, hydrogen peroxide (H 2 O 2 ) and electrolyte leakage which affects rice growth and performance (Yu et al 2013;Srivastava et al 2014). Cadmium toxicity also altered leaf and root ultrastructure and caused structural damages to photosynthetic apparatus of rice.…”
Section: Introductionmentioning
confidence: 99%